Utilization of parboiled rice polish based diet with supplementation of phytase and carbohydrase in growing ducklings (Journal of the Bangladesh Agricultural University, 2012)
A total of 60 day old straight run pekin ducklings were fed ad libitum on 6 diets viz, D1- 15% parboiled rice polish (PRP) based diet, D2- D1 + Mixed enzyme (Carbohydrase 120 ppm/kg + phytase 1000FYT/kg), D3- 25% parboiled rice polish (PRP) based diet, D4 - D3 + Mixed enzyme ( Carbohydrase 120 ppm/kg + phytase 1000FYT/kg), D5-35%   parboiled rice polish (PRP) based diet, D6 - D5+ Mixed enzyme ( Carbohydrase 120 ppm/kg + phytase 1000FYT/kg)  for 84 days. Diets were supplied two stages containing 22.5, 22.5, 22.8% CP for starter and 16.4, 16.9, 17% CP for finisher. Increasing PRP levels without enzyme decreased live weight, feed intake and feed conversion but increase  profitability without affecting livability. Addition of mixed enzyme promoted growth, feed conversion significantly  (P